Training Future International Clinical Academic Leaders Through a Structured Observership Program: Impact and Outcomes from the Initial Cohort. Issue 1 (8th June 2022) - Kuc, Karen J.; Roberts, David H.; Caballero, Augusto Enrique
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Clinical observership programs have existed for many years as both formal initiatives organized at the institutional or professional society level and informal arrangements between individual physicians and prospective mentors. However, few programs longitudinally assess their impact on patient care and require implementation of a postobservership project to demonstrate learning. In 2018, the Harvard Medical School Office for External Education launched the International Clinical Leaders Observership Program (ICLOP) as an opportunity for midcareer physicians to shadow Harvard Medical School faculty in one of three specialty areas: oncology, cardiology, or diabetology. The culminating activity for each participant was presentation of a capstone project and commitment to implement it on returning home. Methods: We summarize here the initial cohort and results from a follow-up survey measuring the impact of the program on their subsequent patient care, academic activities, and achievements. Results: At 1 year of follow-up, 90% of survey respondents had implemented their project. Improvements were reported in areas of clinical, surgical, therapeutic, system, patient education, and team innovation, as well as personal benefits to the participants. Discussion: ICLOP is a robust and reproducible initiative that resulted in meaningful improvements in patient care and physician-related outcomes for the first cohort of participants.